Conatus, the Will to Persist: An Introduction - Özel, Jasmin; Psarros, Nikos (Conatus - Journal of Philosophy, 2021)
The papers collected in this issue address a variety of aspects of the concept of conatus ranging from the explorations of its roots in early ancient Greek thought to its application on modern theories of democratic education. The conatus is a special relation between the parts of a monad and their subparts and the subparts of the subparts to infinity, which ensures that each part and subpart is a part of this monad and not of any other. As a fundamental trait of monadic existence, the conatus is manifested in a multiplicity of facets that sustain the persistence of any real existence. It is thus obvious that there is still a vast field of such manifestations of conatus that awaits philosophical exploration, especially in the realms of Social Ontology and of the Philosophy of Nature.